2015
DOI: 10.1090/conm/639/12827
|View full text |Cite
|
Sign up to set email alerts
|

Uniformization of simply connected finite type Log-Riemann surfaces

Abstract: We consider a log-Riemann surface S with a finite number of ramification points and finitely generated fundamental group. The log-Riemann surface is equipped with a local holomorphic difffeomorphism π : S → C. We prove that S is biholomorphic to a compact Riemann surface with finitely many punctures S, and the pull-back of the 1-form dπ under the biholomorphic map φ : S → S is a 1-form ω = φ * dπ with isolated singularities at the punctures of exponential type, i.e. near each puncture p, ω = e h · ω 0 where h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…In [4], it is shown that a log-Riemann surface of finite type (which has at least one infinite order ramification point) is of the form (S , π), where S is a punctured compact Riemann surface S = S − {p 1 , . .…”
Section: Definition 22 -A Log-riemann Surface Is Of Finite Type If mentioning
confidence: 99%
See 3 more Smart Citations
“…In [4], it is shown that a log-Riemann surface of finite type (which has at least one infinite order ramification point) is of the form (S , π), where S is a punctured compact Riemann surface S = S − {p 1 , . .…”
Section: Definition 22 -A Log-riemann Surface Is Of Finite Type If mentioning
confidence: 99%
“…, p n . As described in [4], each puncture p j corresponds to an end of the log-Riemann surface where d j infinite order ramification points are added, d j being the order of the pole of h j at p j . Let w * be an infinite order ramification point associated to a puncture p j .…”
Section: Definition 22 -A Log-riemann Surface Is Of Finite Type If mentioning
confidence: 99%
See 2 more Smart Citations
“…We study this problem in the simplest situation of genus 0, i.e., we assume that S × is simply connected. Then S × is parabolic and biholomorphic to C (see [4,5]). Also we proved there (see also the early work by R. Nevanlinna [13,14] and M. Taniguchi [18,19]) that we have an explicit formula for the uniformizationF : C → S × that is given by an entire function F = π •F of the form F (z) = Q(z)e P (z) dz, (1.1) where P and Q are polynomials of respective degrees d 1 and d 2 , where d 1 , resp.…”
Section: Introductionmentioning
confidence: 99%